Improving the Students’ Vocabulary by Using Duolingo at Seventh Grade of SMP Negeri 2 Gunungsitoli Utara - Zega, Yudika Syukurniati; Daeli, Hidayati; Laoli, Adieli; Harefa, Trisman (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This research aimed to improve the students’ vocabulary mastery by using the Duolingo application at the seventh grade of SMP Negeri 2 Gunungsitoli Utara. This study employed Classroom Action Research (CAR) consisting of two cycles, and each cycle was conducted in two meetings. The subjects of this research were 26 students of class VII-B. The instruments used in collecting data were observation sheets, field notes, and vocabulary tests. The results showed a significant improvement in students’ vocabulary mastery after the implementation of Duolingo. In the pre-test, only 5 students (19.23%) achieved the Minimum Competency Criteria (MCC) with an average score of 48.46. In Cycle I, the number of students who reached the MCC increased to 14 students (53.85%) with an average score of 61.92. Furthermore, in Cycle II, all students (26 students or 100%) successfully achieved the MCC with an average score of 81.15. The findings also revealed positive changes in students’ learning behavior. The students became more active, confident, motivated, and enthusiastic in learning English vocabulary. They were able to learn independently, practice pronunciation, and respond well to the interactive features provided by Duolingo. Therefore, it can be concluded that the use of Duolingo is effective in improving students’ vocabulary mastery and learning motivation.